Reasons to be cheerful: Personal, civic, and economic achievements after resolving an alcohol or drug problem in the United States population - Eddie, David (Psychol Addict Behav, 2021)
OBJECTIVE: Alcohol and other drug (AOD) use disorders impose a prodigious personal and societal burden. While most remit, little is known about the achievements accrued as people accomplish and sustain addiction recovery. Greater knowledge regarding the nature and prevalence of such achievements, when such achievements occur, what factors influence accrual of achievements, and how such achievements relate to other indices of functioning would support treatment and policy planning, and may instill hope for individuals and families seeking AOD problem resolution. METHODS: Nationally representative, cross-sectional survey of United States (US) population of persons who have overcome an AOD problem (N=2,002), assessing individual factors and achievements in four domains: self-improvement; family engagement; civic, and economic participation. Logistic and linear regression models tested theorized associations among variables. RESULTS: Most (80.1%) achieved at least one achievement associated with the four domains. A linear monotonic relationship was observed with greater achievements accruing with greater time in recovery. Accrual of achievements after AOD problem resolution was related to racial minority status, more education, earlier age of substance use initiation, illicit drugs as primary substance used, more years since resolving AOD problem, more psychiatric diagnoses, lower psychological distress, and regular 12-step program attendance. Multiple regression analyses found greater total achievements was independently associated with greater self-esteem, happiness, quality of life, and recovery capital. CONCLUSIONS: Most individuals achieve an increasing number of achievements with time since AOD problem resolution, and these are associated with gains in measures of well-being that may support ongoing AOD problem remission, and recovery.